Diagnostic value of mean platelet volume in neonatal sepsis - Kristopher May Pamudji; I Made Kardana (Paediatrica Indonesiana, 2019)
Background Neonatal sepsis is a severe disease with potentially serious impacts if not treated early. However, the symptoms and clinical signs are not specific. Several studies have been conducted to find early infection markers for detection of neonatal sepsis, but without satisfactory results. Mean platelet volume (MPV) is a new marker of infection that has good potential for diagnosing neonatal sepsis. Objective To assess the diagnostic value of MPV in early detection of neonatal sepsis. Methods This retrospective study with diagnostic testing was done with data collected from medical records of neonates with neonatal sepsis who were admitted to the Neonatology Department in Sanglah Hospital, Denpasar from December 2018 to March 2019. Mean platelet volume cut-off point was determined using a receiver-operating characteristic (ROC) curve. Sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of MPV in neonatal sepsis were determined using a 2x2 table. Results Of 82 subjects, 55 subjects were male (67%). Positive blood culture results were found in 25 subjects (30%). Mean platelet volume with a cut-off point of 7.44 fL had 80% sensitivity, 84.2% specificity, 69% PPV, and 90.6% NPV. Conclusion Mean platelet volume with a cut-off point of 7.44 fL can be used to diagnose neonatal sepsis with a sensitivity of 80% and specificity of 84.2%.